تأثير الضرائب العثمانية على الجوانب الاقتصادية والاجتماعية في ولاية طرابلس الغرب في العهد العثماني الثاني (Journal of Humanitarian and Applied Sciences, 2016)
The paper refers to this aspect on account of the sources relied upon by the Ottoman state in the provision of general expenses in our dependence on Tajabih of taxes or monopoly of certain good , So it did not tolerate the creation of a strict system for the continuation of this process without regard to economic conditions , social and living conditions of residents of those states which form a drain on the capacity of the population and the U.S. was a factor that hindered the progress of many professions and trades of economic ,And the Ottoman Empire has taken a lot of repairs to this aspect in an attempt to provide as much as possible comes from taxes on her commitment to use the system and the system Alofana addition to the grant categories of social structure such as the elderly, scientists and military personnel in order to aid in tax collection compared to half of them ,In addition to issuing several laws related to this topic, such as land law and the law of Tabu and others, the paper has aimed to clarify the nature and diversity of Tilt taxes and the extent of the damage caused by the economic and social construction in the state of Tripoli , And adopted the paper to adopt a method of analysis based on historical sources and references on the subject, either the most important findings of the paper, it includes a reference to the extent of the damage caused by this process on the economic and social development through the creation of differences between population ,In addition to the damage to pasture land and the population flees from the registration of their land as well as the operations of the census because they were associated with the collection of taxes, as we refer to the set of problems that occurred between individuals or tribes, because of the use of force in the collection of taxes.